Neurometabolic alterations in bipolar disorder with anxiety symptoms: A proton magnetic resonance spectroscopy study of the prefrontal whiter matter. (May 2021) - Chen, Jiayue; Zou, Shaohong; Qu, Yuan; Zhang, Cheng; Zhang, Yi; Tang, Xiaoxiao; Ren, Yongfang
Highlights: This study sought to analyze the differences of brain biochemical metabolism in bipolar disorder patients with and without anxiety symptoms. Bipolar disorder patients with anxiety symptoms have increased levels of inositol metabolism in the right prefrontal whiter matter. The level of membrane phospholipid catabolism in the left prefrontal whiter matter of bipolar disorder patients with anxiety symptoms decreased with increasing age and onset age. Abstract: To identify the pathophysiological mechanism of bipolar disorder (BD) patients with anxiety symptoms, we analyzed the differences of brain biochemical metabolism in BD patients with and without anxiety symptoms. We collected 39 BD patients who had been untreated with drugs in one month and were divided into the anxiety symptoms group (20 cases) and non-anxiety symptoms group (19 cases) according to whether they had anxiety symptoms. We used proton magnetic resonance spectroscopy ( 1 H-MRS) to detect the biochemical metabolite ratios of the prefrontal whiter matter (PWM) in all patients. The right PWM mI/Cr ratios in BD patients with anxiety symptoms were higher than those in BD patients without anxiety symptoms and the Cho/Cr ratios in the left PWM were negatively correlated with age and age of onset in BD patients with anxiety symptoms. These findings indicated that BD patients with anxiety symptoms have increased levels of inositol metabolism in the right PWM. Furthermore, the level of membrane phospholipid catabolism in the left PWM of BD patients with anxiety symptoms decreased with increasing age and onset age. Our results provide some references for the pathophysiological mechanism in BD patients with anxiety symptoms.